Reversal of shortened platelet survival in rats by the antifibrinolytic agent, epsilon aminocaproic acid. - Winocour, P D (1983)
Platelet survival in rabbits and rats is shortened by placing indwelling catheters in the aorta; this shortening appears to be at least partly related to the extent of vessel wall injury and platelet interaction with the repeatedly damaged wall. Treatment of rabbit platelets with plasmin and other proteolytic enzymes in vitro shortens their survival when they are returned to the circulation. Because platelets may be exposed to plasmin and other proteolytic enzymes in rabbits and rats with indwelling aortic catheters, we examined the effect of epsilon-aminocaproic acid (EACA) on platelet survival in rats. At a dose of 1 g/kg every 4 h, EACA significantly reduced whole blood fibrinolytic activity and prolonged the shortened platelet survival in rats with indwelling aortic catheters. Mean platelet survival for untreated rats with indwelling aortic catheters was 38.6 +/- 1.9 h, and for rats treated with EACA, 53.8 +/- 3.8 h. Scanning electron microscopy showed that the injured vessel wall of these animals was mainly covered with platelets and fibrin, whereas in control animals that did not receive EACA, the injured surface was mainly covered with platelets and little fibrin was observed. Thus shortened platelet survival during continuous vessel wall injury may result from the local generation of plasmin or the release of proteolytic enzymes at sites where platelets (and possibly leukocytes) interact with the vessel wall.